2017
DOI: 10.1161/jaha.117.007157
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide–Dependent Feedback Loop Regulates Transient Receptor Potential Vanilloid 4 (TRPV4) Channel Cooperativity and Endothelial Function in Small Pulmonary Arteries

Abstract: BackgroundRecent studies demonstrate that spatially restricted, local Ca2+ signals are key regulators of endothelium‐dependent vasodilation in systemic circulation. There are drastic functional differences between pulmonary arteries (PAs) and systemic arteries, but the local Ca2+ signals that control endothelium‐dependent vasodilation of PAs are not known. Localized, unitary Ca2+ influx events through transient receptor potential vanilloid 4 (TRPV4) channels, termed TRPV4 sparklets, regulate endothelium‐depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
138
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(143 citation statements)
references
References 80 publications
(225 reference statements)
5
138
0
Order By: Relevance
“…Functionally, higher resting astrocyte Ca 2+ levels were associated with augmented levels of PA tone as lowering Ca 2+ within the astrocytic syncytium decreased tone with a greater effect observed in hypertension (Figure 2g). A number of mechanisms could increase astrocyte Ca 2+ during Ang II-induced hypertension including: direct Ang II actions on astrocytes, mechanotransduction via increased stretching of astrocyte processes (as those evoked during adjustments in PA diameter; Kim et al, 2015) and/or via the action of endothelium-mediated signals [e.g., nitric oxide (Kohler et al, 2006;Marziano et al, 2017;Mendoza et al, 2010) and EETs (Dunn et al, 2013;Earley et al, 2009;Vriens et al, 2005)]. Based on poor evidence for AT1R expression in cortical astrocytes and established Ang II-induced endothelial dysfunction (Chrissobolis, Banfi, Sobey, & Faraci, 2012;Chrissobolis, Miller, Drummond, Kemp-Harper, & Sobey, 2011;De Silva et al, 2016;Girouard, Park, Anrather, Zhou, & Iadecola, 2007), we propose hypertension increases the sensitivity of mechanosensitive TRPV4 channels expressed on astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Functionally, higher resting astrocyte Ca 2+ levels were associated with augmented levels of PA tone as lowering Ca 2+ within the astrocytic syncytium decreased tone with a greater effect observed in hypertension (Figure 2g). A number of mechanisms could increase astrocyte Ca 2+ during Ang II-induced hypertension including: direct Ang II actions on astrocytes, mechanotransduction via increased stretching of astrocyte processes (as those evoked during adjustments in PA diameter; Kim et al, 2015) and/or via the action of endothelium-mediated signals [e.g., nitric oxide (Kohler et al, 2006;Marziano et al, 2017;Mendoza et al, 2010) and EETs (Dunn et al, 2013;Earley et al, 2009;Vriens et al, 2005)]. Based on poor evidence for AT1R expression in cortical astrocytes and established Ang II-induced endothelial dysfunction (Chrissobolis, Banfi, Sobey, & Faraci, 2012;Chrissobolis, Miller, Drummond, Kemp-Harper, & Sobey, 2011;De Silva et al, 2016;Girouard, Park, Anrather, Zhou, & Iadecola, 2007), we propose hypertension increases the sensitivity of mechanosensitive TRPV4 channels expressed on astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that TRPV4-mediated sparklets underlie ATP driven activation of endothelial NOS in mouse small pulmonary arteries. The resulting NO initiates vasodilation and also guanylyl cyclase-protein kinase G signaling in the endothelium that limits TRPV4 channel cooperativity and serves as a negative feedback signal to regulate TRPV4 channel function [17]. This description of ATP-evoked, spatially distinct TRPV4 sparklets and localized TRPV4-NOS signaling support a novel paradigm that NOS can be activated by spatially restricted Ca 2+ signals, and identifies TRPV4 channels as a key regulator of NOS activity in the pulmonary microcirculation.…”
Section: Nomentioning
confidence: 55%
“…This idea is supported by the demonstration that in rat pulmonary arteries, vasodilation to the TRPV4 agonist GSK1016790A was mediated by activation of SK Ca channels [52]. In the same vessels, and in mouse small pulmonary arteries, shear stress-stimulated TRPV4 activity was also linked to NO production [17] suggesting a further link between TRPV4 and NOS.…”
Section: Stimulus-specific Endothelial Ca 2+ Signaling 21 Shear Stressmentioning
confidence: 88%
See 2 more Smart Citations